PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Malihatus Sa'diah, Malihatus Sa'diah; Helmita, Helmita; Yusda, Desi Derina (Jurnal Bisnis Darmajaya, 2025)
This study aims to determine the effect of workload and work environment on employee performance at Perum DAMRI Lampung Branch. In a dynamic work environment, workload and workplace conditions are key factors that influence employee productivity. This research uses a quantitative approach with a survey method and questionnaire as the data collection instrument. The population in this study includes all administrative employees of Perum DAMRI Lampung Branch, with a sample size of 62 respondents. Data analysis was conducted using validity and reliability tests, multiple linear regression analysis, partial (t-test), and simultaneous (F-test) testing. The results show that workload has a positive and significant effect on employee performance. Similarly, the work environment also has a positive and significant effect on employee performance. Simultaneously, workload and work environment significantly affect employee performance, contributing 59.3%, while the remaining percentage is influenced by other factors outside this study. These findings highlight the importance of proportional workload management and a supportive work environment to improve employee performance. This study is expected to serve as a reference for Perum DAMRI management in formulating policies to enhance work quality and employee well-being.